Analýza migrace obyvatelstva v Královéhradeckém kraji - Lukešová, Hana (Univerzita Pardubice, 2006)
Tato práce se zabývá migrací v ČR. Pojednává jak o vnitřní, tak o mezinárodní migraci. V teoretické části jsou vysvětleny základní typy prostorového pohybu obyvatelstva. Dále je zde popsán vývoj, objem a struktura vnitřní a mezinárodní migrace v ČR. Druhá část práce je pak zaměřena na migrační procesy Královéhradeckého kraje.

This work occupies with migration in the Czech Republic. It deals with inside and international migration. In theoretical part the basic type of cutic movement of population is explained. Further the progress, quantity and structure of inside and international migration in the Czech Republic is described. The second part is aimed at migration processes Královéhradecký region.
Analysis of migration of population Královéhradecký region
Keywords: inside migration; international migration; region of Hradec Králové; Migration; imigrace; Královéhradecký kraj; emigrace; saldo; Migrace